The use of theory in designing a nursing qualitative research - Jamil, Nurul Akma; Abdul Rashid, Nor'ain; Lee, Khuan (Otjivanda Presse.Bochum, 2023)
Background: For researchers, it is crucial to understand how theory is used when undertaking research because this gives an explanation of the flow of the research and facilitates the translation of the research outcomes into practice. Purpose: The foundation of our article is based on the explanation of how to utilise theory inductively or deductively throughout the journey of undertaking qualitative research. Discussion: In quantitative research, testing hypotheses theoretically is the main use of theory. Meanwhile, questions of when and how to use a theory could be contention in qualitative research. An ongoing debate on the interrelationship and interdependence between theory and research has caused confusion, especially for novice qualitative researchers. Conclusion: This article may benefit novice qualitative researchers by providing a kick-start to incorporate theory in their research work